Shear-Induced CCN1 Promotes Atheroprone Endothelial Phenotypes and Atherosclerosis. Issue 25 (18th June 2019) - Hsu, Pei-Ling; Chen, Jheng-Sin; Wang, Chin-Yung; Wu, Hua-Lin; Mo, Fan-E
Abstract : Background: Atherosclerosis occurs preferentially at the blood vessels encountering blood flow turbulence. The matricellular protein CCN1 is induced in endothelial cells by disturbed flow, and is expressed in advanced atherosclerotic lesions in patients and in the Apoe −/− mouse model. The role of CCN1 in atherosclerosis remains undefined. Methods: To assess the function of CCN1 in vivo, knock-in mice carrying the integrin α6β1–binding-defective mutant allele Ccn1-dm on the Apoe −/− background were tested in an atherosclerosis model generated by carotid artery ligation. Additionally, CCN1-regulated functional phenotypes of human umbilical vein endothelial cells, or primary mouse aortic endothelial cells isolated from wild-type and Ccn1 dm/dm mice, were investigated in the in vitro shear stress experiments under unidirectional laminar shear stress (12 dyn/cm 2 ) versus oscillatory shear stress (±5 dyn/cm 2 ) conditions. Results: We found that Ccn1 expression was upregulated in the arterial endothelium 3 days after ligation before any detectable structural changes, and intensified with the progression of atherosclerotic lesions. Compared with Apoe −/− controls, Ccn1 dm/dm / Apoe −/− mice were remarkably resistant to ligation-induced plaque formation (n=6). These mice exhibited lower oxidative stress, expression of endothelin-1 and monocyte chemoattractant protein-1, and monocyte homing. CCN1/α6β1 critically mediated flow-induced activation of the pleiotropic transcription factor nuclear factor-κB and therefore the induction of atheroprone gene expression in the mouse arterial endothelium after ligation (n=6), or in cultured human umbilical vein endothelial cells or primary mouse aortic endothelial cells exposed to oscillatory shear stress (n=3 in triplicate). Interestingly, the activation of nuclear factor-κB by CCN1/α6β1 signaling prompted more production of CCN1 and α6β1. Blocking CCN1-α6β1 binding by the Ccn1-dm mutation or by T1 peptide (derived from an α6β1-binding sequence of CCN1) disrupted the positive-feedback regulation between CCN1/α6β1 and nuclear factor-κB, and prevented flow-induced atheroprone phenotypic alterations in endothelial cells or atherosclerosis in mice. Conclusions: These data demonstrate a causative role of CCN1 in atherosclerosis via modulating endothelial phenotypes. CCN1 binds to its receptor integrin α6β1 to activate nuclear factor-κB, thereby instigating a vicious circle to persistently promote atherogenesis. T1, a peptide antagonist selectively targeting CCN1-α6β1, can be further optimized for developing T1-mimetics to treat atherosclerosis. Abstract : Supplemental Digital Content is available in the text.